IDENTIFYING ELEMENTARY STUDENTS’ MOTIVATION OF ART EDUCATION LEARNING PROCESS - Anton Sitepu (Jurnal Review Pendidikan dan Pengajaran (JRPP), 2023)
The pursuit of education as a fundamental goal transcends a variety of backgrounds and is an idea that is generally accepted and encountered in daily life. Importantly, the necessary level of education in society requires a growth in student comprehension, which is accomplished by improving educational facilities throughout the learning process. Through supervision, instruction, and training in their chosen fields, this extensive educational journey plays a crucial role in preparing students for future endeavors. The study explores the complex interaction of internal and environmental factors influencing student motivation through a descriptive survey technique using questionnaires. Talent, focus, interest, and health are internal elements that interact with teaching methods, educational resources, and environmental impacts on the outside. Data analysis demonstrates the importance of these components, with environmental influences, learning aids, and instructional methods working together to motivate students. The study sheds light on the varied landscape of student motivation, particularly in the context of art education, at the end. This study not only stresses the differences in student motivation levels but also shows the opportunity for educators to increase motivation through creative educational strategies and interesting materials. The results show that, despite the fact that motivation might vary, its crucial function in generating academic zeal and brilliance is undeniable.